UJI EFEKTIVITAS EKSTRAK KULIT BATANG PULAI (Alstonia scolaris) TERHADAP HAMA Plutella xylostella - Yustina Maria Silvia Wonga Puu (Agriculture Faculty of Flores University, 2014)
The aim of this study is to find out the effectiveness and concentration of Pulai stem extract (Alstoniascolaris) upon the pest of Plutellaxylostella. This study was conducted in the Laboratory of Agriculture Faculty of Flores University in Ende. A completely random design was employed with five treatments, namely J0 (aquades), J1 (75 ml of Pulai stem extract concentration), J2 (100ml of Pulai stem extract concentration), J3 (125ml of Pulai stem extract concentration), J4 (150ml of Pulai stem extract concentration).The result of study reveals that extract of PulaiAlstoniascolaris stem was influential to the development of Plutellaxylostella pest in contact poison of J0 7,50%, J1 60,00%, J2 67,50%, J3 67,50% and J4 80,00%, while for repellant activity of J0 80,00%, J1 57,50%, J2 22,50%, J3 15,00%, and J4 15,00%, for belly poison of J0 00,00%, J1 57,50%, J2 72,50%, J3 75,00% and J4 80,00%. Extract of Pulai stem is the right plant which is effective to highest mortality of Plutellaxylostellapest, belly poison on80,00% of J4 treatment, repellant activity on 15% of J4 treatment, and contact poison on 70% of J4 treatment.